HLH-1 Modulates Muscle Proteostasis During Caenorhabditis elegans Larval Development - Nisaa, Khairun; Ben-Zvi, Anat (Frontiers in Cell and Developmental Biology, 2022)
Muscle proteostasis is shaped by the myogenic transcription factor MyoD which regulates the expression of chaperones during muscle differentiation. Whether MyoD can also modulate chaperone expression in terminally differentiated muscle cells remains open. Here we utilized a temperature-sensitive (ts) conditional knockdown nonsense mutation in MyoD ortholog in C. elegans, HLH-1, to ask whether MyoD plays a role in maintaining muscle proteostasis post myogenesis. We showed that hlh-1 is expressed during larval development and that hlh-1 knockdown at the first, second, or third larval stages resulted in severe defects in motility and muscle organization. Motility defects and myofilament organization were rescued when the clearance of hlh-1(ts) mRNA was inhibited, and hlh-1 mRNA levels were restored. Moreover, hlh-1 knockdown modulated the expression of chaperones with putative HLH-1 binding sites in their promoters, supporting HLH-1 role in muscle maintenance during larval development. Finally, mild disruption of hlh-1 expression during development resulted in earlier dysregulation of muscle maintenance and function during adulthood. We propose that the differentiation transcription factor, HLH-1, contributes to muscle maintenance and regulates cell-specific chaperone expression post differentiation. HLH-1 may thus impact muscle proteostasis and potentially the onset and manifestation of sarcopenia.